LAYANAN BIMBINGAN PRIBADI-SOSIAL UNTUK SISWA YANG MEMILIKI KONSEP DIRI NEGATIF DI SMK NEGERI 7 GARUT - Sri Hartati; Heris Hendriana; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The concept of one's self includes knowledge, judgment, and expectations about one's physical, psychic, and social self. The concept of self can shape the cognitive structure of students to do things, either doing positive actions or doing negative actions. This research was conducted using qualitative approach with a case study method. The purpose of this research is to describe the implementation of social personal guidance services for students who have negative self-concepts in SMK N 7 Garut. The data collected in this study are data obtained by interviewing, observation and documentation studies. The results showed that students who have negative self-concept who follow social personal guidance services at SMK N 7 Garut including AF and AR students still need guidance services in terms of knowledge and assessment, while from the aspect of expectations AF and AR students already have a positive self-concept. It is necessary the sustainability of social personal guidance servicesKeywords: social-personal guidance services, self concept